Relationship between soil fertility and plantain nutrition in Cundinamarca (Colombia) with the incidence of two bacterial diseases (2020)
Bacteriosis and moko of plantain are two of the more important phytosanitary problems in musaceae production in Colombia. To contribute to the management of these diseases in the Department of Cundinamarca, soils and foliar tissues were analyzed, along with symptoms of the diseases on 149 producing farms in the municipalities of Chaguani, La Palma, La Vega, and Viota (Cundinamarca). A descriptive analysis of the chemical properties of the soils and foliar concentration of nutrients was carried out; the Student-Welch t-test was applied (P<0.05); the distribution patterns of the diseases were represented cartographically. According to the results, the sampled soils were not saline and had extreme to strong acidity, low effective cation exchange capacity and low fertility; meanwhile, the plants presented a deficit of elements such as nitrogen, phosphorus, sulfur, copper, zinc, and boron. Considering the total number of farms evaluated, the incidence of bacteriosis and moko disease was reported in 63 and 14% at the departmental level, respectively. A higher concentration of sulfur and zinc was observed in farm soils free of both diseases. Finally, the plants free of bacteriosis showed a higher concentration of potassium and lower concentrations of calcium and manganese, while the plants free of moko disease showed higher concentrations of nitrogen, sodium, and copper and a lower concentration of calcium. The results can contribute to the planning of large-scale management strategies to reduce the risk of the dissemination of diseases of economic importance for plantain crops.